Obstacle avoidance behavior of swarm robots based on aggregation and disaggregation method. (November 2017) - Yu, Yue; Chen, Xiangru; Lu, Zhaohan; Li, Fengxia; Zhang, Bo
One of the current challenges in the development of swarm robots is making them realize obstacle avoidance while keeping formation. This paper proposes a new obstacle avoidance method for multiple robots based on the aggregation and disaggregation approach. First, the formation-based multi-resolution models of swarm robots are presented and the formation attribute-based consistency mapping functions are designed. Then, obstacle avoidance behavior based on aggregation and disaggregation method is presented and the basic obstacle avoidance behaviors are designed. Finally, the simulation results are presented to show the feasibility of the proposed method.